2008
DOI: 10.1080/13803390701551225
|View full text |Cite
|
Sign up to set email alerts
|

Impairments in phonological processing and nonverbal intellectual function in parents of children with autism

Abstract: Language difficulties have been implicated to be a part of the broad autism phenotype in first-degree relatives of individuals with autism. Phonological processing difficulties in particular have been reported by some, but not all groups studying parents or siblings of probands with autism. In the present study, we examined a broad battery of language tasks and general cognitive abilities in parents of children with autistic disorder. Parents of individuals with autism (n = 22) were compared to matched adult c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 47 publications
1
41
0
1
Order By: Relevance
“…Researchers also reported on language and communication difficulties in parents of individuals with autism, including a history of language-related difficulties (e.g., language delay, difficulties in articulation, reading, and spelling), structural language difficulties (e.g., phonological processing deficits), as well as difficulties in pragmatic language abilities or the social use of language (Bishop et al 2006;Folstein et al 1999;Fombonne et al 1997;Landa et al 1992;Piven and Palmer 1997;Schmidt et al 2008;Tager-Flusberg and Joseph 2003;Whitehouse et al 2007). Pragmatic language abilities are usually characterized as the use of language appropriate to social context including conversational turn-taking, appropriate use of references, coherence, topic maintenance, and aspects of speech such as prosody and fluency, as well as nonverbal features such as communicative eye contact, facial expressions, and gestures.…”
Section: Introductionmentioning
confidence: 98%
“…Researchers also reported on language and communication difficulties in parents of individuals with autism, including a history of language-related difficulties (e.g., language delay, difficulties in articulation, reading, and spelling), structural language difficulties (e.g., phonological processing deficits), as well as difficulties in pragmatic language abilities or the social use of language (Bishop et al 2006;Folstein et al 1999;Fombonne et al 1997;Landa et al 1992;Piven and Palmer 1997;Schmidt et al 2008;Tager-Flusberg and Joseph 2003;Whitehouse et al 2007). Pragmatic language abilities are usually characterized as the use of language appropriate to social context including conversational turn-taking, appropriate use of references, coherence, topic maintenance, and aspects of speech such as prosody and fluency, as well as nonverbal features such as communicative eye contact, facial expressions, and gestures.…”
Section: Introductionmentioning
confidence: 98%
“…29 The analysis of reading and writing acquisition revealed that the difficulties of some parents of children with autism seem to be associated with an abnormal development of language rather than with autism. Parents of individuals with autism were less capable of discriminating subtle differences between faces and had more difficulties in identifying expressions of fear and disgust than typically-developing individuals …”
Section: Cognitive Modelsmentioning
confidence: 99%
“…These can be related to: the practical use of language (Ben-Yizhak et al, 2011;Bolton et al, 1994;Bishop et al, 2004;Landa et al, 1992;Losh, Childres, Lam, & Piven, 2008;Folstein et al, 1999;Ruser et al, 2007), syntax (Bishop et al, 2006), reading and understanding (Piven & Palmer, 1997), as well as general communication skills (Bishop et al, 2004;Ruser et al, 2007;Wheelwright, Auyeung, Allison, & Baron-Cohen, 2010;Whitehouse, Barry, & Bishop, 2007). However, research is not conclusive, and some studies do not confirm the existence of language or communication deficits among the relatives of individuals with ASD (Folstein et al, 1999;Pilowsky et al, 2003;Schmidt et al, 2008).…”
Section: Discussionmentioning
confidence: 99%